Compositional methods for information-hiding†. (24th November 2014) - CHATZIKOKOLAKIS, KONSTANTINOS; PALAMIDESSI, CATUSCIA; BRAUN, CHRISTELLE
Abstract : Systems concerned with information hiding often use randomization to obfuscate the link between the observables and the information to be protected. The degree of protection provided by a system can be expressed in terms of the probability of error associated with the inference of the secret information. We consider a probabilistic process calculus to specify such systems, and we study how the operators affect the probability of error. In particular, we characterize constructs that have the property of not decreasing the degree of protection, and that can therefore be considered safe in the modular construction of these systems. As a case study, we apply these techniques to the dining cryptographers, and we derive a generalization of Chaum's strong anonymity result.